2016
DOI: 10.1177/0956462416666753
|View full text |Cite
|
Sign up to set email alerts
|

Men who have sex with men diagnosed with a sexually transmitted infection are significantly more likely to engage in sexualised drug use

Abstract: The sexualised use of recreational drugs (Mephedrone, GBL/GHB, Crystal Meth) generally known as 'chemsex' in men who have sex with men (MSM) is thought to be associated with sexually transmitted infection (STI) acquisition; however there is little data showing a direct relationship. We reviewed 130 randomly selected cases of MSM with an STI attending our STI service and 130 controls (MSM attending the STI service who did not have an STI) between 5 May 2015 and 2 November 2015. Reported condomless anal sex was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 11 publications
2
29
0
12
Order By: Relevance
“…Previous work in the UK has shown that, among HIVpositive MSM, recreational drug use, regardless of the sexual context, is associated with condomless sex, including with partners of unknown or HIV-negative status, creating the possibility for HIV transmission [13,14]. Drug use has also been linked to outbreaks of Shigella flexneri 3a among MSM in London [15] and an increased incidence of bacterial STIs and hepatitis C [12,[16][17][18]. Reports from urban centres such as London and Bristol suggest that chemsex is increasing in popularity [6,8,19,20], is more common among HIV-positive than HIV-negative MSM [7,8,13,16], and may be linked to HIV transmission [9,13,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in the UK has shown that, among HIVpositive MSM, recreational drug use, regardless of the sexual context, is associated with condomless sex, including with partners of unknown or HIV-negative status, creating the possibility for HIV transmission [13,14]. Drug use has also been linked to outbreaks of Shigella flexneri 3a among MSM in London [15] and an increased incidence of bacterial STIs and hepatitis C [12,[16][17][18]. Reports from urban centres such as London and Bristol suggest that chemsex is increasing in popularity [6,8,19,20], is more common among HIV-positive than HIV-negative MSM [7,8,13,16], and may be linked to HIV transmission [9,13,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sex and drug use is long established, however the use of drugs in sexual contexts (sexualised drug use) has potential implications for public health. Sexualised drug use (SDU) has been associated with risky sexual behaviours (Digiusto & Rawstorne, 2013;Hegazi et al, 2017;Nodin, Valera, Ventuneac, Maynard, & Carballo-Dieguez, 2011;, increasing the likelihood of participation in condomless sex and thus the risk of sexually transmitted infection (STI) or blood borne virus (BBV) transmission (Olufon & Cathcart, 2016;Ottaway, Finnerty, Amlani, et al, 2017;Page & Nelson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…No consensus European definition is available. Certain studies have found chemsex to be associated with a number of HIV risk factors such as multiple sexual partners, group sex and condomless sex in men who have sex with men (MSM) [ 2 4 ]. One study found an association between chemsex and incident sexually transmitted infections (STIs) in HIV-infected individuals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%